Microbiological Quality and Proximate Composition of Bakasang Laor, a Traditional Fermented Fishery Product in Maluku - Ferymon Mahulette; Tri Santi Kurnia (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Bakasang laor is one of the traditional fermented fishery products in Maluku, Indonesia. There are two types of bakasang laor, i.e. with and without vinegar. The microbiological research of bakasang processed use laor as raw material has never been done before. The research aimed to analyze the microbiological quality and proximate composition of two types of bakasang laor. The proximate composition can determine the nutritional value of this product for consumption by the community. The sample of bakasang laor was taken from traditional producer in Latuhalat village, Ambon. The total number of halotolerant and coliform bacteria in bakasang laor without vinegar were 1.7x106 CFU/g and 4.1x106 CFU/g, respectively, while the total of lactic acid bacteria in bakasang laor with vinegar was 6.0x106 CFU/g. The carbohydrate, protein, fat and ash contents of bakasang laor with vinegar was higher than bakasang laor without vinegar. The carbohydrate, protein and fat contents of bakasang laor with vinegar were 19.64 %, 16.23 %, and 2.42 %, respectively. Generally, microbiological quality and proximate composition of bakasang laor with vinegar was better than bakasang laor without vinegar. The bacteria that play a role in fermentation can be used as a starter in the fermentation of various food products. The results of this research to improve the quality of this fermentation product in the future.